TREATMENT OF NECROTIC ENTEROCOLITIS IN NEWBORN CHILDREN - A. E. Solov’Ev; I. A. Anikin; A. P. Pakhol’Chuk (Вестник хирургии имени И.И. Грекова)
Necrotic enterocolitis is a common disease of the newborn children, which requires an emergency treatment. The results of children treatment depend on many factors, especially from well-timed diagnostics in case of transition from therapeutic to surgical stage. There was noted the tendency to lethality reduction because of necrotic enterocolitis (17% in developed countries, 42% in countries with low- and middle levels of economy) over the past decade. The authors followed-up 42 children with the diagnosis of necrotic enterocolitis. Sepsis, inflammatory bowel disease, toxic products in its lumen are the main source of severe condition of the child. The antibacterial and detoxication therapies should be performed for the newborn child with necrotic enterocolitis on admission to the hospital. An operative treatment have to be carried out in case of lack of condition improvement.